Ventricular noncompaction: Over or under diagnosis? - Ali, Sulafa K.M. (2009)
Ventricular noncompaction (VNC) describes a cardiomyopathy characterized by excessive myocardial trabeculations and deep intertrabecular recesses. Detection rates are increasingly rising and the frequency of NVC has changed from a disease that is thought to be rare to that described as ‘relatively common’. However, there had been a number of un-answered questions regarding the clinical and echocardiographic features of VNC. In this review we discuss the frequency of VNC and emphasize its distinctive clinical features and associations.